A golden opportunity : advancing California's early care and education workforce professional development system - Karoly, Lynn A., 1961- (Rand Corporation monograph series., 2012)
This study focuses on the education, training, and ongoing professional development of early care and education (ECE) caregivers, teachers, and administrators who work with infants, toddlers, and preschool-age children from birth to kindergarten entry in California. It aims to provide a comprehensive assessment of the state's ECE workforce professional development system and a set of recommendations for improving the system's effectiveness.